Financial Performance Assessment of PT Bukit Uluwatu Villa Tbk in Comparison with other Hosptality Companies in Indonesia - Hanafi, Kevin; Damayanti, Sylviana Maya (Journal of Business and Management, 2015)
Abstarct. One of Indonesia’s hospitality companies is PT Bukit Uluwatu Villa Tbk. This study will assess the financial performance of PT Bukit Uluwatu Villa Tbk as a company mainly operated in the island of Bali and carry the concept of green resort. The assessment will be done with Financial Ratio Analysis, Compound Annual Growth Rate (CAGR) analysis, and DuPont System of Analysis. PT Bukit Uluwatu Villa Tbk will be compared to 4 other listed hospitality company in Indonesia which are PT Grahamas Citrawisata Tbk, PT Hotel Mandarine Regency Tbk, PT Pembangunan Graha Lestari Indah Tbk, dan PT Sahid Jaya International. The result of the analysis shows that PT Bukit Uluwatu Villa Tbk has some generally good condition with several weak points. One of them is average payment period. Some recommendation that can be given is to increase the price of the room or to increase the number of room to boost their assets.Keywords:Financial Ratio, Compound Annual Growth Rate, DuPont System of Analysis, Financial Performance